Legal Remedies Against Distributor Companies for Pending Payment - Azkiya, Nailur Rohmatul; Bahagiati, Kurniasih (Et-Tijarie, 2024)
Relationship between CV distributors. New Nirvana and its retailers are bound by an agreement. The agreement agreed upon by both parties is a written agreement, in the form of a sales invoice. The agreement uses a cash, transfer, or tempo COD (Cash on Delivery) payment system with a deadline of one week. However, some retailers made promises and asked for more time. Therefore, the purpose of the study is to find out the implementation of the CV distribution service payment agreement. Nirwana Baru with retail stores, and reviewing legal remedies against CV. Nirwana Baru for late payment and default by retail stores. This type of research is juridical empiric research with a qualitative approach. The data source consists of primary data and secondary data. The data collection method consists of observation, interviews, literature studies, and documentation. Based on the results of the research, it is known that the implementation of the payment agreement for CV distributors. New Nirwana uses three payment methods: cash, transfer, and tempo COD systems. Retailers who delay payments with the tempo system are very detrimental to distributors because they interfere with the company's financial operations. Then the legal efforts carried out by CV. New Nirwana when there is a default by a retail store is a non-litigation effort, namely deliberation or mediation. Because the company chose not to take this matter to court, as well as the absence of strong evidence as a legal basis. As a result, retailers who are in default are not subject to civil sanctions such as compensation fines. But in reality, CV. Nirwana Baru has never taken the path of litigation or legal.